Kajian Peran Gen P53 dalam Tumorigenesis - Retina Yunani (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2016)
Gene p53 is a tumor suppressor gene that in normal conditions is in ' standby ' mode , several studies show that pivotal point that lead to stimulation of p53 is DNA damage , heat shock , hypoxia, exposure of nitric oxide ( NO ) , the expression of oncogenes and some p53 pathways activation. p53 mechanism as a guardian of genome stability are cell cycle arrest, repair of DNA damaged, induce apoptosis, prevents angiogenesis , invasion and metastasis ability of the tumor. On many tumor , p53 is not loss , but mutated , the p53 mutant was expressed 70 % in lung cancer , and in different frequencies in other cancers . Then the role of p53 as a transcription factor that works to regulate genes involved in tumor suppression is indispensable .